Exercise-associated hyponatremia during winter sports - Stuempfle, K. J. (The Physician and Sportsmedicine, 2010)
Exercise-associated hyponatremia (EAH) is hyponatremia that occurs = 24 hours after prolonged physical activity. It is a potentially serious complication of marathons, triathlons, and ultradistance events, and can occur in hot and cold environments. Clear evidence indicates that EAH is a dilutional hyponatremia caused by excessive fluid consumption and the inappropriate release of arginine vasopressin. Cerebral and pulmonary edema can cause serious signs and symptoms, including altered mental status, respiratory distress, seizures, coma, and death. Rapid diagnosis and urgent treatment with hypertonic saline is necessary to prevent severe complications or death. Prevention is based on educating athletes to avoid excessive drinking before, during, and after exercise.